Musahamah al-Lughah al-'Arabiyah fi Taqadum al-Tsaqafah wa al-Hadharah al-Urubiyah - Efendi, Aprijon; Pamil, Jon; Promadi, Promadi; Alwizar, Alwizar (Arabi : Journal of Arabic Studies, 2024)
During the era of the advancement of Islamic civilization in Andalusia, Arabic became the language of teaching sciences, and it was very popular among Europeans to learn it. From there, science developed rapidly in Europe, producing many well-known experts in their fields and even coloring world civilization. In this article, the researcher tried to reveal the great and wonderful contribution of the Arabic language to the advancement of European culture and civilization. This contribution has not been revealed superficially before and many people do not know it in detail, as Arabic is one of the oldest languages in the Levantine language family. In this research, a qualitative approach was used with the design of an interpretive model that seeks to understand and interpret the meaning of a reality in the form of a phenomenon about the influence of the Arabic language on the progress of European culture and civilization. The data obtained as analytical material is through observation, documentation, and interviews. In the end, it makes clear that the Arabic language has contributed enormously to the social, cultural, economic, technological, educational and civilizational progress achieved by European countries today.